The vulnerability of the human world: well-being, health, technology and the environment - Boublil, Élodie; Ferrarello, Susi (Springer International Publishing, 2023)
Part 1. Critical history and critical phenomenology of Health and Well-being -- Chapter 1. Global Health and the Collateral Damage Utilitarianism (Kelly Oliver) -- Chapter 2. Why does mental illness exist? Considerations on anthropological vulnerability (Thomas Fuchs) -- Part 2. Well-Being, Health and Embodiment -- Chapter 3. The Ontological and Ethical Value of Vulnerability (Valeria Bizzari) -- Chapter 4. Well-Being, Health, and Human Embodiment: The Familial Lifeworld (Mark J. Cherry) -- Part 3. Well-Being, Health and the Environment -- Chapter 5. Being and Aging: A Phenomenology of Time, Place and Illness (Marjolein Oele) -- Chapter 6. Vulnerability, Mutual Aid, Empathy (Gerard Kuperus) -- Part 4. The Vulnerability of the Human World and Responsibility -- Chapter 7. Pandemic Discrimination and Responsibility for Culturally Vulnerable Groups. A Phenomenological and Bioethical Perspective (Geoffrey Dierckxsens) -- Chapter 8. Interdependency, responsibility and the care for the living (Elodie Boublil) -- Part 5. The vulnerability of the human world. Health, technology and the environment -- Chapter 9. From digital medicine to embodied care (Francesca Brencio) -- Chapter 10. Aiming at Well-Being with Brain Implants: Any risk of Implanting Unprecedented Vulnerabilities? (Frederic Gilbert) -- Chapter 11. Phenomenology of algorithms and emotions in cases of early re-hospitalization (Susi Ferrarello) -- Chapter 12. Conclusion.